Impaired regulation of brain serotonin function during dieting in women recovered from depression. - Smith, K; Williams, C; Cowen, P (2000)
BACKGROUND: Amino acid mixtures that lower brain availability of the serotonin (5-HT) precursor tryptophan produce acute depressive relapse in women with a history of major depression. Dieting also lowers brain tryptophan availability, but its effects on brain 5-HT function in recovered depressed women have not been studied. AIM: To test the hypothesis that women with a history of major depression would show impaired regulation of brain 5-HT function during a period of dieting-induced tryptophan depletion. METHOD: Women with and without a history of major depression were placed on a daily 1000 kcal (approximately 4200 kj) diet for three weeks. Before the diet and in the final week we measured fasting plasma tryptophan levels and the prolactin response to an intravenous tryptophan challenge. RESULTS: Dieting lowered plasma tryptophan levels equivalently in women with and without a history of depression. In women without a history of depression, dieting also increased the prolactin response to tryptophan. This increase did not occur in women with a history of depression. CONCLUSIONS: Women with a history of depression showed impaired regulation of brain 5-HT function in response to dieting.